Steel material for automobile and method for manufacturing same

By adjusting the steel composition and process steps, a dual-phase steel with high content of ferrite and martensite is formed, which solves the problem of insufficient work hardening rate of existing steel and achieves the application requirements of high stamping forming and the deformation prevention effect.

CN119332165APending Publication Date: 2025-01-21CHINA STEEL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410307674.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-03-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The work hardening rate of existing duplex steels is difficult to meet the needs of high stamping forming of automotive parts, and local deformation is prone to occur during stamping.

Method used

By adjusting the contents of carbon, silicon, manganese, chromium, molybdenum, aluminum, phosphorus and sulfur, and using specific process steps, such as heating, hot rolling, cold rolling, annealing and over-aging processes, the volume fraction is at least 50% Dual-phase steel with a ferrite structure and a balanced martensite structure.

Benefits of technology

The work hardening rate of automotive steel is significantly increased to at least 0.15, meeting high stamping forming requirements and avoiding local deformation during the stamping process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332165A_ABST
    Figure CN119332165A_ABST
Patent Text Reader

Abstract

The invention relates to steel for an automobile and a manufacturing method of the steel. The steel for the automobile contains ferrite and martensite in a specific proportion, so that the work hardening rate of the steel for the automobile can be increased, and certain tensile strength, yield strength and ductility are maintained. The steel for the automobile can meet the application requirement for high-stamping forming of automobile parts and components, local deformation in the stamping process is avoided, concave resistance is kept, and the absorbing capacity of collision energy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel material for automobiles and a method for manufacturing the same, and more particularly to a steel material for automobiles having a dual-phase structure including a ferrite structure and a martensite structure and a method for manufacturing the same. Background Art

[0002] Dual-phase steel has the characteristics of high strength, low yield ratio, good bake hardenability and high work hardening rate. The high work hardening rate can avoid local deformation during stamping, while the low yield ratio and good bake hardenability are conducive to forming, while maintaining dent resistance and improving the ability to absorb collision energy.

[0003] Although dual-phase steel can solve the contradiction between high strength and formability, as the automotive industry continues to develop towards collision safety and lightweight body, the existing dual-phase steel work hardening rate can no longer meet the needs of stamping forming of some automotive parts.

[0004] Therefore, there is an urgent need to provide a steel material for automobiles and a manufacturing method thereof to solve the defects of the existing conventional steel materials for automobiles. Summary of the invention

[0005] In view of this, one aspect of the present invention is to provide a steel material for automobiles, and another aspect of the invention is to provide a method for manufacturing steel material for automobiles, so as to improve the work hardening rate of the steel material and meet the application requirements of high stamping forming of automobile components, thereby avoiding local deformation of the steel material during the stamping process.

[0006] At least one embodiment of the present invention provides a steel material for automobiles. Based on 100 parts by weight of the total weight of the steel material for automobiles, the steel material for automobiles comprises 0.08 to 0.2 weight percent of carbon, 0.2 to 1.0 weight percent of silicon, 1.0 to 2.5 weight percent of manganese, 0.02 to 0.7 weight percent of chromium, 0.02 to 0.155 weight percent of molybdenum, 0.02 to 0.05 weight percent of aluminum, no more than 0.02 weight percent of phosphorus, no more than 0.015 weight percent of sulfur, and the remainder of iron and unavoidable impurities, wherein the steel material for automobiles comprises a dual-phase structure consisting of a ferrite structure with a volume fraction of at least 50% and a balance of martensite structures, and a work hardening rate of the steel material for automobiles is at least 0.15.

[0007] In at least one embodiment of the present invention, the dual-phase structure is composed of a ferrite structure with a volume fraction of 50% to 60% and a martensite structure with a volume fraction of 40% to 50%.

[0008] In at least one embodiment of the present invention, the grain size of the ferrite structure is greater than 4 μm.

[0009] In at least one embodiment of the present invention, the tensile strength of the automobile steel is at least 780 MPa, and the yield strength of the automobile steel is at least 400 MPa.

[0010] In at least one embodiment of the present invention, the elongation of the automotive steel is at least 16%.

[0011] At least one embodiment of the present invention provides a method for manufacturing automobile steel, comprising the following steps. A steel billet is provided, wherein the steel billet comprises 0.08 to 0.2 weight percent carbon, 0.2 to 1.0 weight percent silicon, 1.0 to 2.5 weight percent manganese, 0.02 to 0.7 weight percent chromium, 0.02 to 0.155 weight percent molybdenum, 0.02 to 0.05 weight percent aluminum, no more than 0.02 weight percent phosphorus, no more than 0.015 weight percent sulfur, and the remainder iron and unavoidable impurities, based on the total weight of the steel billet as 100 parts by weight. A heating step is performed on the steel billet. After the heating step, a hot rolling step is performed on the steel billet to obtain a hot-rolled steel sheet. A cold rolling step is performed on the hot-rolled steel sheet to obtain a cold-rolled steel sheet, wherein the cold rolling rate of the cold rolling step is at least 40%. The cold rolled steel sheet is subjected to an annealing step and cooled to 300°C at a cooling rate of 5°C / sec to 14°C / sec, wherein the annealing holding temperature of the annealing step is 770°C to 830°C, and the annealing time of the annealing step is 2 minutes to 4 minutes. After the annealing step, an aging process is performed to obtain an automotive steel material, wherein the automotive steel material comprises a dual-phase structure, the dual-phase structure is composed of a ferrite structure with a volume fraction of at least 50% and a martensite structure with a balance, and the work hardening rate of the automotive steel material is at least 0.15.

[0012] In at least one embodiment of the present invention, in the aforementioned heating step, the heating temperature of the heating step is 1150° C. to 1300° C., and the heating step is maintained at the temperature for 2 hours to 4 hours.

[0013] In at least one embodiment of the present invention, in the aforementioned hot rolling step, the finishing temperature of the hot rolling step is 880°C to 950°C, and the coiling temperature of the hot rolling step is 500°C to 700°C.

[0014] In at least one embodiment of the present invention, the method for manufacturing the automobile steel further comprises performing a pickling step on the hot-rolled steel sheet before the cold rolling step.

[0015] In at least one embodiment of the present invention, in the aforementioned over-aging process, the processing temperature of the over-aging process is 150° C. to 300° C., and the processing time of the over-aging process is 7 minutes to 20 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] When read in conjunction with the accompanying drawings, aspects of the present invention will be fully understood. The dimensions of the various features may be arbitrarily increased or reduced for the purpose of clarity of discussion.

[0017] Figure 1 This is a scanning electron microscope image of the automobile steel material according to Experimental Example 2 of the present invention.

[0018] Figure 2 This is a scanning electron microscope image of the automobile steel material according to Comparative Example 1 of the present invention.

[0019]

Main component symbol description

[0020] α: Ferrite structure

[0021] M: Martensite structure DETAILED DESCRIPTION

[0022] The manufacture and use of the embodiments of the present invention are discussed in detail below. However, it is to be understood that the embodiments provide many applicable inventive concepts that can be implemented in a variety of specific contexts. The specific embodiments discussed are for illustration only and are not intended to limit the scope of the present invention.

[0023] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values ​​in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as if the arbitrary value and the smaller numerical range were explicitly written in the specification.

[0024] In some embodiments of the present invention, a steel material for automobiles is provided, the steel material for automobiles comprising carbon, silicon, manganese, chromium, molybdenum, aluminum, phosphorus, sulfur, and the remainder of iron and inevitable impurities. The obtained steel material for automobiles is a dual-phase steel, and its metallographic structure contains a dual-phase structure composed of a specific ratio of ferrite structure and martensite structure, wherein the grain size of the ferrite structure is greater than 4 μm, and the work hardening rate of the steel material for automobiles can be increased to meet the application requirements of high stamping forming of automobile components.

[0025] The types and contents of the aforementioned elements, after being processed by a specific process, affect the tensile strength, yield strength, elongation, work hardening rate and metallographic structure of the automotive steel. The tensile strength of the automotive steel of the present invention is at least 780 MPa. The yield strength of the automotive steel of the present invention is at least 400 MPa. The elongation of the automotive steel of the present invention is at least 16%.

[0026] The work hardening rate (n 4-6 ) is at least 0.15. It should be noted that the term "work hardening rate (n 4-6 )" is the work hardening rate when the ratio of stress to strain is between 4% and 6%.

[0027] In the above embodiments, the specific ratio is defined by volume fraction, however, in other embodiments, the specific ratio may be defined in other ways, such as area fraction, etc. In some embodiments, the dual-phase structure of the automotive steel is composed of a ferrite structure with a volume fraction of at least 50% and a balance of martensite structure. In other embodiments, the dual-phase structure of the automotive steel is composed of a ferrite structure with a volume fraction of 50% to 60% and a martensite structure with a volume fraction of 40% to 50%. When the volume fraction of the ferrite structure of the automotive steel is less than 50%, the automotive steel with specific strength, elongation and work hardening rate of the present invention cannot be formed.

[0028] In some embodiments of the present invention, based on 100 parts by weight of the total weight of the automobile steel, the automobile steel comprises 0.08 to 0.2 weight percent of carbon, 0.2 to 1.0 weight percent of silicon, 1.0 to 2.5 weight percent of manganese, 0.02 to 0.7 weight percent of chromium, 0.02 to 0.155 weight percent of molybdenum, 0.02 to 0.05 weight percent of aluminum, not more than 0.02 weight percent of phosphorus, not more than 0.015 weight percent of sulfur, and a balance of iron and unavoidable impurities.

[0029] In some specific examples, the automobile steel contains 0.1, 0.12, 0.14, 0.16 or 0.18 weight percent of carbon. When the carbon content is less than 0.08 weight percent or greater than 0.2 weight percent, the dual-phase steel with a specific dual-phase structure of the present invention cannot be formed.

[0030] In some specific examples, the automotive steel includes, for example, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9 weight percent silicon. In the embodiments of the present invention, the addition of silicon can reduce the stacking fault energy (SFE) of the steel, so that during the formation of the steel, the dislocation is not easy to cross slip, and the formed ferrite structure has a high dislocation density structure, thereby improving the work hardening rate (n) of the automotive steel. 4-6 When the silicon content in the automobile steel is less than 0.2 weight percent, the differential energy of the steel cannot be reduced, and the dual-phase steel with a specific dual-phase structure of the present invention cannot be formed, so the work hardening rate of the automobile steel cannot be increased (n 4-6 ). When the silicon content in the automobile steel is greater than 1.0 weight percent, during the process of forming the steel, the austenite structure (γ) is not easy to form the martensite structure, so the dual-phase steel with a specific dual-phase structure of the present invention cannot be formed.

[0031] In some specific examples, the automobile steel contains 1.2, 1.4, 1.6, 1.8, 2, 2.2 or 2.4 weight percent manganese. When the manganese content is less than 1.0 weight percent or greater than 2.5 weight percent, the dual-phase steel with a specific dual-phase structure of the present invention cannot be formed.

[0032] In some specific examples, the automobile steel contains 0.1, 0.2, 0.3, 0.4, 0.5 or 0.6 weight percent of chromium. When the chromium content is less than 0.02 weight percent or greater than 0.7 weight percent, the dual-phase steel with a specific dual-phase structure of the present invention cannot be formed.

[0033] In some specific examples, the automotive steel contains, for example, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, and 0.15 weight percent of molybdenum. In an embodiment of the present invention, the addition of molybdenum can increase the hardening energy, making it difficult for the steel to generate other metallographic structures during the heat treatment process, so that the volume fraction of the martensite structure can be maintained at a specific ratio, thereby forming a specific dual-phase structure of the present invention. In other words, the addition of molybdenum can ensure that the high-temperature austenite structure (γ) can be transformed into a martensite structure. In detail, when the molybdenum content in the automotive steel is less than 0.02 weight percent, the hardening energy of the steel is insufficient, so the high-temperature austenite structure (γ) is prone to produce a ferrite structure (α), and the formed steel cannot meet the application requirements. When the molybdenum content in the automotive steel is greater than 0.155 weight percent, the hardening energy will be too high, and the generated steel will have too much martensite structure, while reducing the content of ferrite structure, so it is impossible to form a steel with a work hardening rate (n 4-6 ) is above 0.15 for automobile steel.

[0034] In some specific examples, the steel for automobiles contains, for example, 0.03 or 0.04 weight percent aluminum. Aluminum is mainly used for deoxidation during steelmaking.

[0035] In some specific examples, the automobile steel contains no more than 0.02 weight percent phosphorus, no more than 0.015 weight percent sulfur, and unavoidable impurities. It should be understood that the phosphorus and sulfur of the present invention are impurities in the steel, and the unavoidable impurities referred to herein in the present invention refer to impurities that cannot be separated during the smelting process.

[0036] It is worth noting that in the above-mentioned embodiments, the automotive steel of the present invention does not contain niobium, which has the effect of grain refinement. When niobium is additionally added to the automotive steel of the present invention, it is impossible to form a ferrite structure with a grain size greater than 4 μm, thereby reducing the work hardening rate of the automotive steel.

[0037] Some embodiments of the present invention provide a method for manufacturing an automobile steel material. The aforementioned manufacturing method comprises heating a steel billet, hot rolling the steel billet to obtain a hot-rolled steel plate, pickling the hot-rolled steel plate, cold rolling the hot-rolled steel plate to obtain a cold-rolled steel plate, annealing the cold-rolled steel plate to obtain a cooled steel plate, and performing an aging process on the cooled steel plate to obtain the automobile steel material of the present case.

[0038] In the aforementioned manufacturing method, first, a steel billet is provided. In some embodiments, based on the total weight of the steel billet as 100 parts by weight, the steel billet contains 0.08 to 0.2 weight percent carbon, 0.2 to 1.0 weight percent silicon, 1.0 to 2.5 weight percent manganese, 0.02 to 0.7 weight percent chromium, 0.02 to 0.155 weight percent molybdenum, 0.02 to 0.05 weight percent aluminum, no more than 0.02 weight percent phosphorus, no more than 0.015 weight percent sulfur, and the remainder iron and unavoidable impurities. The influence of the element types and contents of the aforementioned steel billet on the tensile strength, yield strength, elongation, work hardening rate and metallographic structure of the automobile steel is as described above, and will not be repeated here. In addition, the aforementioned heating step, hot rolling step, pickling step, cold rolling step, annealing step and over-aging process also affect the tensile strength, yield strength, elongation, work hardening rate and metallographic structure of automobile steel.

[0039] The aforementioned heating step is to make the steel billet produce austenite to facilitate the subsequent hot rolling step. In some embodiments, the heating step is to heat the steel billet to 1150°C to 1300°C and hold the temperature for 2 hours to 4 hours. When the steel billet is heated to 1150°C to 1300°C, all elements in the steel billet can be completely dissolved, which is beneficial to the subsequent hot rolling of the steel billet.

[0040] After the aforementioned heating step, the steel billet is subjected to a hot rolling step to obtain a hot-rolled steel plate, wherein the finishing temperature of the hot rolling step is 880° C. to 950° C., and the coiling temperature of the hot rolling step is 500° C. to 700° C. In some embodiments, after the aforementioned hot rolling step, the hot-rolled steel plate is then subjected to a pickling step to remove the hot rolling scale on the surface of the hot-rolled steel plate.

[0041] Next, the hot rolled steel sheet is subjected to a cold rolling step to obtain a cold rolled steel sheet, wherein the cold rolling rate of the cold rolling step is at least 40%. When the cold rolling rate is less than 40%, the metallographic structure of the automotive steel will be uneven, which will affect the tensile strength, yield strength, elongation and work hardening rate of the subsequently formed automotive steel.

[0042] Then, an annealing step is performed on the cold-rolled steel sheet, wherein the annealing holding temperature of the annealing step is 770° C. to 830° C., and the annealing time of the annealing step is 2 minutes to 4 minutes.

[0043] After the annealing step, the annealed cold-rolled steel sheet is subjected to a cooling step to obtain a cooled steel sheet. The cooling rate of the cooling step is 5°C / sec to 14°C / sec, and the cooling temperature of the cold-rolled steel sheet is 300°C. When the cooling rate is less than 5°C / sec, the too slow cooling rate causes too much ferrite phase in the formed automotive steel, resulting in insufficient strength of the steel. When the cooling rate is greater than 14°C / sec, the too fast cooling rate causes insufficient ferrite phase in the formed automotive steel, resulting in excessive strength of the steel.

[0044] The cooled steel plate is subjected to an over-aging process, and after cooling to room temperature, the automotive steel of the present invention can be obtained, wherein the treatment temperature of the over-aging process is 150°C to 300°C, and the treatment time of the over-aging process is 7 minutes to 20 minutes. When the over-aging process is performed, the structure in the steel tends to be stable, and the internal stress generated during the steel manufacturing process can be effectively eliminated, thereby improving the mechanical properties of the steel. When the treatment temperature is less than 150°C, the martensite tempering effect is reduced, the tensile strength of the steel is increased, and the yield strength is reduced. When the treatment temperature is greater than 300°C, the martensite tempering effect is increased, and the tensile strength of the steel is reduced. When the treatment time is less than 7 minutes, the martensite tempering effect is reduced, the tensile strength of the steel is increased, and the yield strength is reduced. When the treatment time is greater than 20 minutes, the martensite tempering effect is increased, and the tensile strength of the steel is reduced.

[0045] When the steel billet having the specific composition content is used and the manufacturing method is used to manufacture the automobile steel, the metallographic structure of the automobile steel contains a ferrite structure with a volume fraction of at least 50% and a martensite structure with a balance, wherein the grain size of the ferrite structure is greater than 4 μm, the tensile strength is at least 780 MPa, the yield strength is at least 400 MPa, the elongation is at least 16%, and the work hardening rate (n 4-6 ) is at least 0.15.

[0046] In short, the automobile steel of the present invention can be used as automobile steel by adjusting the contents of carbon, silicon, manganese, chromium, molybdenum, aluminum, phosphorus and sulfur and specific process conditions to form a dual-phase steel with a specific ratio of ferrite structure and martensite structure. The grain size of the ferrite structure of the automobile steel of the present invention is greater than 4μm, and the work hardening rate (n 4-6 ) is at least 0.15, which can meet the application requirements of high stamping forming of automotive components.

[0047] The following experimental examples are used to illustrate the application of the present invention, but they are not used to limit the present invention. Anyone skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention.

[0048] Experimental Example 1

[0049] In Experimental Example 1, the steel billet contained 0.09 weight percent of carbon, 0.48 weight percent of silicon, 1.95 weight percent of manganese, 0.51 weight percent of chromium, 0.02 weight percent of molybdenum, 0.042 weight percent of aluminum, 0.009 weight percent of phosphorus, 0.003 weight percent of sulfur, and the remainder of iron and inevitable impurities.

[0050] The aforementioned steel billet is heated to 1250°C and held at this temperature for 2 to 4 hours. Then, a hot rolling step is performed to obtain a hot-rolled steel sheet, wherein the finishing temperature is 907°C and the coiling temperature is 580°C. Then, the hot-rolled steel sheet is subjected to a cold rolling step to obtain a cooled steel sheet, wherein the cold rolling rate is 48%. Then, the cold-rolled steel sheet is subjected to an annealing step to obtain a cooled steel sheet, wherein the annealing holding temperature is 830°C, the annealing time is 2 to 4 minutes, the cooling rate is 11.3°C / second, and the cooling temperature is 300°C. Finally, the cooled steel sheet is subjected to an over-aging process and cooled to room temperature to obtain a steel material for automobiles, wherein the over-aging treatment temperature is 150 to 300°C and the treatment time is 9.3 minutes. The automobile steel material obtained in Experimental Example 1 is evaluated in the evaluation method described below, and the evaluation results are shown in Table 1, wherein "α" contained in the metallographic structure represents a ferrite structure, and "M" represents a martensite structure.

[0051] Experimental Examples 2 to 3 and Comparative Examples 1 to 3

[0052] Experimental Examples 2 to 3 and Comparative Examples 1 to 3 were conducted in a similar manner to Experimental Example 1. The difference is that the element content and process parameters of the steel billet were changed in Experimental Examples 2 to 3 and Comparative Examples 1 to 3. The specific parameter conditions and evaluation results of Experimental Examples 2 to 3 and Comparative Examples 1 to 3 are shown in Tables 1 and 2, respectively.

[0053] Table 1

[0054]

[0055] Table 2

[0056]

[0057]

[0058] Evaluation method

[0059] 1. Measurement of metallographic structure

[0060] The metallographic structure of the present invention is measured by using a scanning electron microscope to capture images of the automobile steel of each experimental example and comparative example, and measuring the area percentage of the ferrite structure and the martensite structure in the image, and taking the average of the 5 obtained area percentages as the volume fraction, the unit of which is %. The measurement results of the metallographic structure of the automobile steel of the above-mentioned experimental example and comparative example are shown in Table 1, and Figure 1 The scanning electron microscope image of the automobile steel material of Experimental Example 2 is shown. Figure 2 This is a scanning electron microscope image of the automobile steel material of Comparative Example 1. Figure 1 and Figure 2 , the symbol "α" indicates a ferrite structure, and the symbol "M" indicates a martensite structure.

[0061] 2.α grain size

[0062] The α grain size of the present invention is measured by using the scanning electron microscope image of the metallographic structure, and the average grain size of the ferrite structure obtained by the diagonal, horizontal and vertical line measurement method of the standard method ASTM E112 is used as the evaluation result. Figure 1 and Figure 2 As shown, at the same scale, Figure 1 The grain size of the ferrite structure (α) is significantly larger than Figure 2 The grain size of the ferrite structure.

[0063] 3. Tensile strength test

[0064] The tensile strength referred to herein in the present invention is tested according to the standard method JIS Z2241 to measure the tensile strength of the automobile steel materials of Experimental Examples 1 to 3 and Comparative Examples 1 to 3, and the unit is MPa. The measurement results of the tensile strength are shown in Table 1.

[0065] 4. Yield strength test

[0066] The yield strength referred to herein in the present invention is tested according to the standard method JIS Z2241 to measure the yield strength of the automobile steel materials of Experimental Examples 1 to 3 and Comparative Examples 1 to 3, and the unit is MPa. The measurement results of the yield strength are shown in Table 1.

[0067] 5. Elongation test

[0068] The elongation referred to herein in the present invention is tested according to the standard method JIS Z2241, with a gauge length of 50 mm, to measure the elongation of the automobile steel materials of Experimental Examples 1 to 3 and Comparative Examples 1 to 3, in %, and the measurement results of the elongation are shown in Table 1.

[0069] 6. Work hardening rate n 4-6 Trial

[0070] The work hardening rate n referred to herein in the present invention is 4-6 The test was conducted according to the standard method ASTM E646 to measure the work hardening rates of Experimental Examples 1 to 3 and Comparative Examples 1 to 3, and the measurement results of the work hardening rates are shown in Table 1.

[0071] Please refer to Table 1. Compared with the automobile steels of Comparative Examples 1 to 3, the work hardening rates of the automobile steels of Experimental Examples 1 to 3 are all greater than 0.15, which are suitable for high stamping applications and can avoid local deformation of the automobile steels during the stamping process.

[0072] The automobile steel of the present case contains a dual-phase structure of a specific content of ferrite and martensite, wherein the grain size of the ferrite structure is greater than 4 μm, so that the automobile steel of the present case has a tensile strength of at least 780 MPa, a yield strength of at least 400 MPa, an elongation of at least 16%, and a work hardening rate of at least 0.15. The dual-phase automobile steel with a high work hardening rate of the present invention can meet the application requirements of high stamping forming of automobile parts, avoid local deformation during stamping, and maintain dent resistance and improve the ability to absorb collision energy.

[0073] It is to be understood that although the present invention uses specific composition, specific metallographic structure, specific manufacturing method and specific evaluation method as examples to illustrate the automotive steel material and the manufacturing method thereof of the present invention, anyone with ordinary knowledge in the technical field to which the present invention belongs will know that the present invention is not limited thereto, and the present invention may also be carried out using other compositions, other metallographic structures, other manufacturing methods or other evaluation methods without departing from the spirit and scope of the present invention.

[0074] Although the present invention has been disclosed as above in the form of an implementation method, it is not intended to limit the present invention. Anyone with ordinary knowledge in the technical field to which the present invention belongs can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on what is defined in the claims.

Claims

1. A steel material for automobiles, characterized in that: The total weight of the automobile steel material is 100 parts by weight, comprising: 0.08 to 0.2 weight percent carbon; 0.2 to 1.0 weight percent of silicon; 1.0 to 2.5 weight percent manganese; 0.02 to 0.7 weight percent of chromium; 0.02 to 0.155 weight percent of molybdenum; 0.02 to 0.05 weight percent aluminum; Not more than 0.02 weight percent of phosphorus; No more than 0.015 weight percent sulfur; and The remainder is iron and inevitable impurities, wherein the automobile steel comprises a dual-phase structure consisting of a ferrite structure with a volume fraction of at least 50% and a martensite structure of a balance, and the work hardening rate of the automobile steel is at least 0.

15.

2. The automobile steel material according to claim 1, characterized in that: The dual-phase structure is composed of a ferrite structure with a volume fraction of 50% to 60% and a martensite structure with a volume fraction of 40% to 50%.

3. The automobile steel material according to claim 1, characterized in that: The grain size of the ferrite structure is greater than 4 μm.

4. The automobile steel material according to claim 1, characterized in that: The tensile strength of the automobile steel is at least 780 MPa, and the yield strength of the automobile steel is at least 400 MPa.

5. The automobile steel material according to claim 1, characterized in that: The elongation of the automobile steel is at least 16%.

6. A method for manufacturing a steel material for automobiles, characterized in that: Include: A steel billet is provided, wherein, based on 100 parts by weight of the total weight of the steel billet, the steel billet comprises: 0.08 to 0.2 weight percent carbon; 0.2 to 1.0 weight percent of silicon; 1.0 to 2.5 weight percent manganese; 0.02 to 0.7 weight percent of chromium; 0.02 to 0.155 weight percent of molybdenum; 0.02 to 0.05 weight percent aluminum; Not more than 0.02 weight percent of phosphorus; No more than 0.015 weight percent sulfur; and The remainder is iron and unavoidable impurities; Performing a heating step on the steel billet; After the heating step, the steel billet is subjected to a hot rolling step to obtain a hot-rolled steel sheet; Performing a cold rolling step on the hot-rolled steel sheet to obtain a cold-rolled steel sheet, wherein the cold rolling rate of the cold rolling step is at least 40%; The cold-rolled steel sheet is subjected to an annealing step and cooled to 300° C. at a cooling rate of 5° C. / s to 14° C. / s, wherein the annealing holding temperature of the annealing step is 770° C. to 830° C., and the annealing time of the annealing step is 2 minutes to 4 minutes; After the annealing step, an aging process is performed to obtain the automobile steel, wherein the automobile steel comprises a dual-phase structure consisting of a ferrite structure with a volume fraction of at least 50% and a martensite structure with a balance, and the work hardening rate of the automobile steel is at least 0.

15.

7. The method for producing a steel material for automobiles according to claim 6, characterized in that: The heating temperature of the heating step is 1150° C. to 1300° C., and the heating step is maintained at the temperature for 2 hours to 4 hours.

8. The method for producing a steel material for automobiles according to claim 6, characterized in that: The finishing temperature of the hot rolling step is 880°C to 950°C, and the coiling temperature of the hot rolling step is 500°C to 700°C.

9. The method for manufacturing a steel material for automobiles according to claim 6, characterized in that: The method further comprises performing a pickling step on the hot rolled steel sheet before the cold rolling step.

10. The method for manufacturing a steel material for automobiles according to claim 6, characterized in that: The treatment temperature of the over-aging process is 150° C. to 300° C., and the treatment time of the over-aging process is 7 minutes to 20 minutes.